3D printing trends in building and construction industry: a review. Issue 3 (3rd July 2017) - Tay, Yi Wei Daniel; Panda, Biranchi; Paul, Suvash Chandra; Noor Mohamed, Nisar Ahamed; Tan, Ming Jen; Leong, Kah Fai
ABSTRACT: Three-dimensional (3D) printing (also known as additive manufacturing) is an advanced manufacturing process that can produce complex shape geometries automatically from a 3D computer-aided design model without any tooling, dies and fixtures. This automated manufacturing process has been applied to many diverse fields of industries today due to significant advantages of creating functional prototypes in reasonable build time with less human intervention and minimum material wastage. However, a more recent application of this technology towards the built environment seems to improve our traditional building strategies while reducing the need for human resources, high capital investments and additional formworks. Research interest in employing 3D printing for building and construction has increased exponentially in the past few years. This paper reviews the latest research trends in the discipline by analysing publications from 1997 to 2016. Some recent developments for 3D concrete printing at the Singapore Centre for 3D Printing are also discussed here. Finally, this paper gives a brief description of future work that can be done to improve both the capability and printing quality of the current systems.